2021
DOI: 10.1002/eng2.12437
|View full text |Cite
|
Sign up to set email alerts
|

Novel engineering of ruthenium‐based electrocatalysts for acidic water oxidation: A mini review

Abstract: The oxygen evolution reaction (OER) is pivotally involved in proton exchange membrane water electrolyzers (PEMWEs). However, the commercialized iridium‐based catalysts often suffer from severe sluggish kinetics, eventually deteriorating the polarization and overall PEMWEs performance. Therefore, to develop OER electrocatalysts with promising reaction kinetics and high stability is of great significance for PEMWEs. Compared to iridium, the ruthenium‐based catalysts possess lower price and higher activity in aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…The peak at the binding energy of 288.14 eV belongs to the surface-functionalized organic CO bonds. Figure S22b gives the high-resolution XPS spectra of O 1s, where the peaks at binding energies of 529.22, 530.81, 532.3, and 535.1 eV are ascribed to the Ru–O, hydroxyl groups, adsorbed water molecules, and organic C–O bonds, respectively. , The Co 2p orbital does not show any characteristic binding energy peak (Figure S22c), which might be due to the low content of the cobalt ions after OER. From the post-OER analysis, it is observed that the robustness of the catalyst Co-RuO 2 was retained, as proved by means of FE-SEM, HR-TEM, HAADF color mapping, EDS, and XPS analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at the binding energy of 288.14 eV belongs to the surface-functionalized organic CO bonds. Figure S22b gives the high-resolution XPS spectra of O 1s, where the peaks at binding energies of 529.22, 530.81, 532.3, and 535.1 eV are ascribed to the Ru–O, hydroxyl groups, adsorbed water molecules, and organic C–O bonds, respectively. , The Co 2p orbital does not show any characteristic binding energy peak (Figure S22c), which might be due to the low content of the cobalt ions after OER. From the post-OER analysis, it is observed that the robustness of the catalyst Co-RuO 2 was retained, as proved by means of FE-SEM, HR-TEM, HAADF color mapping, EDS, and XPS analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Different crystal planes of the catalyst also exhibit different coordination atoms and surface energies, and the selective exposure of active surfaces on the crystals can significantly improve their electrocatalytic activity [75,76]. For example, two Ir nanocrystals (one with a flat surface enclosed by (100) facets and the other with a concave surface containing numerous high-index planes) were prepared by depositing an Ir capping layer on Pd nanocubes [1]. During the OER process, the concave Ir crystals with high-index planes promoted the formation of the surfactant IrO x , leading to a gradual increase in activity, while the planar Ir crystals surrounded by (100) facets exhibited a gradual decrease in activity.…”
Section: Geometric Effectmentioning
confidence: 99%
“…The growing challenges from the energy crisis and environmental pollution necessitate the development of appropriate renewable energy storage and conversion technologies [1,2]. Renewable energy sources such as wind and solar energy are expected to be an effective way to power the clean and sustainable energy infrastructure [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that with the introduction of foreign elements, such as V, Sn, Co, Ni, Zn, Fe, W, and La, the electronic structure of the Ru site can be modulated and prevent the formation of oxygen vacancies, and thus is effective to improve the stability of Ru-based anode catalysts. 102,103 Recently, Hao et al synthesized the W 0.2 Er 0.1 -Ru 0.7 O 2Àd anode catalyst by bimetallic doping, enabling this catalyst to exhibit long-term stability for 500 h. 104 They found that the W and Er dopants were capable of downshifting the O 2p-band center to the Fermi level, which increased the oxygen vacancy formation energy. The authors believed that the increase of the oxygen vacancy formation energy inhibits the direct O-O coupling together from the lattice of W 0.2 Er 0.1 Ru 0.7 O 2Àd , which makes the OER inclined to the AEM and reduces the tendency of Ru dissolution and oxidation (Fig.…”
Section: Ru-based Anode Catalystsmentioning
confidence: 99%